Assessing Livelihood Adaptation Indices and the Sustainability of Rice Farmers in Bangladesh's Northwestern Region - Eyasmin, Farjana; Ghosh, Bikash Chandra; Adeleye, Bosede Ngozi (Frontiers in Sustainability, 2021)
Climate change alters the impact of the environment on economies and sustainable adaptation which may improve food security is embedded in the actualization of the 2030 United Nations Sustainable Development Goals (SDGs) 2, 13, and 14. Hence, this study contributes to the debate by measuring how farmers in the Northwestern region of Bangladesh adapt to climate change. A cross-sectional multistage random sampling is used to collect 500 data by face-to-face interview method. For robustness, the study demonstrates climate change adaptation, adaptation index, and the sustainability indicators in social, economic, and environmental concepts using the composite indicator method. Also, Rasch analysis and marginal contribution were used to explain the adaptation index. Finally, a trivariate Tobit regression is used to examine sustainability analysis over climate change adaptation strategies and explain how the climate change adaptations affect different dimensions of sustainability. The results showed that most dominating adaptation strategies like irrigation and chemical fertilizer are not sustainable, unlike dominant male households, more prominent families, skilled farmers, and food security influenced adaptation index, and strategies such organic manure, changing planting dates, diseases tolerant varieties, irrigation. The study also found that farm size, credit access, and extension contact significantly affects sustainability. Moreover, off-farm activities, crop diversification, and using high-yielding varieties are more sustainable adaptation strategies. Policy outcomes are discussed.